Cross-infection of adenovirus among medical staff: A warning from the intensive care unit in a tertiary care teaching hospital in China. (September 2020) - Dai, Minhui; Wu, Yanhao; Tan, Hongyi; Deng, Jing; Hou, Maodan; Peng, Wenzhong; Chen, Guo; Li, Yi; Li, Haitao; Pan, Pinhua; Lu, Jingmei
Highlights: Human adenovirus-55 in a single patient had strong transmission potential in ICU. This infectious event involved more than 20 medical staff members in adult ICU. Contact with patient, lack of hand hygiene or gloving adherence, were risk factors. Abstract: Rationale: In 2019, a small HAdV55-associated outbreak of adenovirus infection occurred among the intensive care unit (ICU) staff in Xiangya Hospital of Central South University in Hunan Province, China, during the treatment of a patient. Objective: To investigate the characteristics of a nosocomial adenovirus outbreak in an ICU. Methods: We evaluated all the patients treated and the medical staff working in the ICU from August 1 to September 4, 2019. We further performed an epidemiological and molecular analysis for this outbreak from patient to healthcare workers and between healthcare workers. After the outbreak, we adopted exposure prevention and droplet prevention measures based on standard precautions. Measurements and main results: Between August 1 and August 27, 2019, 27 cases of human adenovirus cross-infection were reported in our institution. Among the cases, eleven were doctors (41%), eleven were nurses (41%), three were respiratory therapists (11%), and two were caregivers (7%). The attack rate was 28.4%, and the fatality rate was 0. The results showed that contact with the index case, lack of hand hygiene or gloving adherence were risk factors for infection after adenovirus exposure. After taking specific precautions, no new cases of infection have appeared since August 27. Conclusions: Our results show that HAdV55 in a single patient had strong transmission potential in an intensive care unit with adequate facilities and standardized operation. We provide convincing evidence indicating that attention could be highlighted on the role of standard and specific precautions for controlling the spread of adenovirus in ICUs.